Efektivitas Penambahan Plant Growth Promoting Bacteria (Azospirillum sp) dalam Meningkatkan Pertumbuhan Mikroalga (Chlorella sp) pada Media Limbah Cair Tahu Setelah Proses Anaerob - Taif Maharsyah; Musthofa Lutfi; Wahyunanto Agung Nugroho (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2013)
Chlorella sp is one of microalgae  that is used as a raw material for biofuels. Hence research that has been committed ( Luz e. De-bashan et al. , 2008 ) Chlorella sp start cultivated by using bacteria supporting plant growth of Azospirillum brasiliense which produces growth hormone IAA.. According to the description, the researcher want to replace species of bacteria and medium, with including a species of bacterium Azospirillum sp and medium tofu wastewater after the anaerobic process. Where the purpose of this study was to determine the effect of adding a dose of bacteria Azospirillum sp on the rate of growth of Chlorella sp carried out in liquid medium waste after anaerobic process. Each treatment is A0 (without the addition of bacteria), A2 (addition bacteria Azospirillum sp 2 x 108 cfu/ ml), A4 (addition of Azospirillum sp 4 x 108 cfu/ml), A6 (addition of Azospirillum sp 6 x 108 cfu/ml ), A8 (addition Azospirillum sp  of 8 x 108 cfu/ml), A10 (addition of Azospirillum sp 109 cfu/ml). From the data obtained indicate the giving of different doses of Azospirillum sp will give the maximum growth rate (μmaks) populations Chlorella sp different also. So the regression test showed a significant effect on the addition or dose rate of growth of bacteria on microalgae. Average of the highest growth rate obtained with the A10 treatment (μmaks) as much as (0.463347sel/hari) and average lowest growth rate obtained with A0 (μmaks) as much as (0.327467 cells / day). While the results of the regression test for support parameters obtained significant results. So dose the addition of different bacteria affect the temperature, pH, and water quality (including nitrate, ammonium, orthophosphate).Kata Kunci: Mikroalga, Chlorella sp, Azospirillum sp, Limbah cair tahu setelah proses anaerob